SURVEY OF BUILDINGS IN THE CITY LESNOY ON THE INDOOR RADON CONCENTRATION - A. M. Marennyy; M. E. Kiseleva; N. A. Nefedov; G. I. Sutiagina; L. E. Karl (Радиационная гигиена)
Survey of the buildings in the Lesnoy city, Sverdlovsk region, on the indoor radon were performed. Measurements of radon volume activity were carried out by integral method using radon track exposimeters REI-4. Exposimeters were installed for measurements at 2–4 months in the heating and warm periods of the year in the same premises. 17 kindergartens, 7 schools, 20 dwelling houses, 22 medical institutions and 3 other institutions were surveyed. The values of the equivalent equilibrium concentration of radon and indoor radon doses are obtained. The results of determining the radon equivalent equilibrium concentration in the premises on different floors of buildings belonging to different groups in the heating and warm period of the year, as well as the estimated average annual values of equivalent equilibrium concentration are presented. Average annual values of equivalent equilibrium concentration for kindergartens, schools, dwellings houses and medical institutions are in the range of 34–51 Bq/m3, and only for other institutions reach 79 Bq/m3. Average values of equivalent equilibrium concentration for all premises of the city Lesnoy were: for the heating period -  46 Bq/m3, for warm – 38 Bq/m3, average annual - 42 Bq/m3. It is shown that both for separate periods and for the annual the ratio of average equivalent equilibrium concentration values in the rooms on the second floors in relation to the first floors of different groups buildings is 0.6–0.8. For higher floors of dwellings houses the radon equivalent equilibrium concentration values does not depend on the floor. This can be explained by both the small statistics of measurements in the rooms on the upper floors and the relatively low values of equivalent equilibrium concentration, that is typical for most buildings of the city. The estimates showed that the average radon concentration in brick houses is less than in slag-block houses: the values of radon equivalent equilibrium concentration – 6 – 188 and 10 – 235 Bq/m3, the average annual values – 41 and 54 Bq/ m3, respectively. Conservative estimates of annual doses of radon in all the surveyed premises do not exceed 10 mSv/year, and the average annual doses for most groups of buildings (kindergartens, schools, dwelling houses, medical institutions) are in the range of 2 – 3 mSv/year, and only for the group «Other institutions» - up to 4 mSv/year.